The effect of music therapy on cancer pain management in palliative care patients : a systematic review - Başıbüyük, Meryem; Yıldırım, Dilek (Gevher Nesibe Sağlık Araştırmaları Merkezi, 2020)
Objective: This systematic review was conducted to investigate the studies which evaluate the effect of music therapy on cancer pain management in palliative care patients. Methods: The studies on cancer pain management, both in English and Turkish, whose full text versions were accessible, were systematically analyzed, the studies without full text were not included. The study was conducted by screening CINAHL EBSCOhost MEDLINE, ScienceDirect, Ovi, ProQuest, Web of Science ULAKBİM National Data Bases. Keywords such as "Cancer Pain", "Cancer Pain Management", "Palliative Care" were used to access the studies. 22 research papers were accessed and 7 of them were found to be compatible with the inclusion criteria of our study. Cohrane was established as the guideline to determine levels of evidence. Results: 5 studies out of 7 that were analyzed during the systematic review were randomized controlled trial; while, one was experimental study, and the other was meta-analysis. When all the study results were analyzed, it was shown that music therapy was effective in reducing the pain. It is informed that music, which has no adverse effect, even in a 20-30 minutes long session, is effective in reducing pain according to the studies that investigate the effects of music in reducing cancer pain. Conclusion: When the effect of music therapy interventions on the physical and psychological recovery of patients who receive palliative care treatment was investigated, it was concluded that music therapy interventions are highly effective in reducing pain, and no adverse effect was found during the study.

Amaç: Bu sistematik derleme, palyatif bakım hastalarında müzik terapinin kanser ağrısı yönetimine etkisini değerlendiren çalışmaları incelemek için yapılmıştır. Yöntem: Kanser ağrısı yönetimine ilişkin Türkçe ve İngilizce tam metnine ulaşılabilen araştırmalar sistematik inceleme kapsamına alınmış tam metin olmayan devam eden çalışmalar kapsam dışı bırakılmıştır. Çalışma CINAHL EBSCOhost MEDLINE, ScienceDirect, Ovi, ProQuest, Web of Science ULAKBİM Ulusal Veri Tabanları tarayarak yürütülmüştür. Çalışmalara ulaşmak için "Kanser Ağrısı", “Kanser Ağrısı Yönetimi", “Müzik Terapi", “Palyatif Bakım” anahtar kelimeleri kullanılmıştır. 22 araştırma makalesine ulaşılmış, bu çalışmaların 7 tanesinin araştırmaya dâhil edilme kriterlerine uygun olduğu belirlenmiştir. Kanıt düzeylerini belirlemede Cohrane rehber alınmıştır. Bulgular: Sistematik derlemede incelenen 7 çalışmanın 5’i randomize kontrollü çalışma, birinin deneysel çalışma ve birinin ise meta-analiz çalışması olduğu görülmektedir. Tüm çalışma sonuçları incelendiğinde müzik terapinin ağrı şiddetini azaltmada etkili olduğunu göstermektedir. Kanser ağrısını azaltmada müziğin etkisini inceleyen çalışmalarda, her hangi bir advers etkisi bulunmayan, müziğin yaklaşık 20-30 dk süresince dinletilmesinin 1 seans dahi olsa ağrıyı azaltmada etkili olduğu bildirilmektedir. Sonuç: Palyatif bakımda tedavi gören kanser hastalarında fiziksel ve psikolojik iyileşmede müzik girişimlerinin etkisi incelendiğinde müzik uygulamalarının ağrıyı büyük oranda azaltıcı etkisi olduğu, çalışma süresince hiçbir advers etkiye rastlanmadığı sonucuna ulaşılmıştır. Anahtar Kelimeler: Kanser ağrısı, kanser ağrısı yönetimi, müzik terapi, palyatif bakım
Palyatif Bakım Hastalarında Müzik Terapinin Kanser Ağrısı Yönetimine Etkisi : Bir Sistematik Derleme
1 PhD Student, Istanbul University-Cerrahpaşa Florence Nightingale Faculty of Nursing, Department of Public Health Nursing, Istanbul, Turkey, mrymbasibuyuk@gmail.com, ORCID No: 0000-0001-5968-9031, Corresponding author -- 2 PhD, İstanbul Sabahattin Zaim University, University Faculty of Health Sciences, Department of Nursing, Istanbul, Turkey, dilek.yildirim@izu.edu.tr, ORCID No: 0000-0002-6228-0007
Keywords: Cancer pain; Cancer pain management; Music therapy; Palliative care; Kanser ağrısı; Kanser ağrısı yönetimi; Müzik terapi; Palyatif bakım